Brain‐derived neurotrophic factor Val66Met polymorphism and early life adversity affect hippocampal volume12. Issue 2 (22nd January 2013) - Carballedo, Angela; Morris, Derek; Zill, Peter; Fahey, Ciara; Reinhold, Elena; Meisenzahl, Eva; Bondy, Brigitta; Gill, Michael; Möller, Hans‐Jürgen; Frodl, Thomas
Abstract The interaction between adverse life events during childhood and genetic factors is associated with a higher risk to develop major depressive disorder (MDD). One of the polymorphisms found to be associated with MDD is the Val66MET polymorphism of brain‐derived neurotrophic factor (BDNF). The aim of our two‐center study was to determine how the BDNF Val66Met polymorphism and childhood adversity affect the volumetric measures of the hippocampus in healthy individuals and people with MDD. In this two‐center study, 62 adult patients with MDD and 71 healthy matched controls underwent high‐resolution magnetic resonance imaging. We used manual tracing of the bilateral hippocampal structure with help of the software BRAINS2, assessed childhood adversity using the Childhood Trauma Questionnaire and genotyped Val66Met BDNF SNP (rs6265). MDD patients had smaller hippocampal volumes, both in the left and right hemispheres (F = 5.4, P = 0.022). We also found a significant interaction between BDNF allele and history of childhood adversity (F = 6.1, P = 0.015): Met allele carriers in our samples showed significantly smaller hippocampal volumes when they did have a history of childhood adversity, both in patients and controls. Our results highlight how relevant stress–gene interactions are for hippocampal volume reductions. Subjects exposed to early life adversity developed smaller hippocampal volumes when they carry the Met‐allele of the BDNF polymorphism. © 2013 Wiley Periodicals, Inc.